EFFECT OF NEUROMUSCULAR ELECTRICAL STIMULATION ON QUADRICEPS MUSCLE STRENGTH AND SIX MINUTE WALK DISTANCE IN SPUTUM NEGATIVE PULMONARY TUBERCULOSIS (International Journal of Physiotherapy, 2015)
Background: Pulmonary Tuberculosis (PTB) leads to many physical impairements which can affect the daily physical tasks. Giving neuromuscular electrical stimulation (NMES) to quadriceps muscle can improve the functional status without causing fatigue and compromising oxygen status. The aim of the study was to study the effect of NMES on quadriceps muscle strength and six minute walk distance in Pulmonary tuberculosis.Method: This was an interventional based study conducted in K.J.Somaiya Medical Hospital. 26 patients suffering from pulmunary tuberculosis were taken in the study. Strength assessment of quadriceps muscle was assessed by 1RM and six minute walk distance was assessed by six minute walk test. NMES is given to quadriceps muscles bilaterally for continuous 10 sessions in 11 days.Result: Wilcoxon signed rank test, ‘t' test and mann whitney test were done to analyse the data. There was significant increase in 1RM (1.808kgs->2.885kgs) and 6MWD (405.23m->493.65m) post NMES training.Conclusion: Therefore the study performed suggest that NMES training performed prior to endurance training is useful for strengthening peripheral muscles, which in turn may augment gains in body weight and improves quality of life, further reductions in ventilation requirements during exercise. Despite the ability to cure tuberculosis, there remains a significant impact on the patient’s health status in physical, psychological and social aspects. The study showed significant improvement by giving NMES in 6MWD and 1RM.